The Effect of Inspiratory Muscle Training (IMT) on Blood Pressure in Late Adults with Hypertension - Husni Husni; widiya lestari; Muhammad Gilang Ilahi (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Hypertension in Indonesia affects 30.8% of adults, with contributing factors including diet, smoking, physical activity, and stress. An initial survey in the Lingkar Timur Community Health Center area found data on 781 adults with hypertension. Based on interviews with 10 hypertensive patients, it was found that they only underwent pharmacological therapy and were unaware that inspiratory muscle training techniques could lower blood pressure. Objectives: The purpose ofithis study was to assess the influence of Inspiratory Muscle Training (IMT) on the blood pressure of hypertensive late adults within the Lingkar Timur Health Center's jurisdiction. Methods: This was a quasi-experimentalistudy with a total sample of 44 participants, divided into an intervention group (n=22) and a control group (n=22). Non-probability sampling with a purposive method was used, selecting respondents based on inclusion criteria: late adult age, systolic blood pressure >140 mmHg, and diastolic blood pressure >90 mmHg. Results: Statistical analysis, utilizing the independent t-test for systolic blood pressure and the Mann-Whitney U test for diastolic blood pressure, revealed a p-value of α≤0.05. This signifies a statistically significant outcome of Inspiratory Muscle Training (IMT) on the blood pressure of hypertensive patients. Conclusion: Inspiratory Muscle Training (IMT) effectively lowers blood pressure for late adults in conjuction with hypertension.